Effects of swimming training on cecum microorganisms and metabolites in rats with high fat diet - Dong, Chuan; Chen, Ling; Li, Dengpan; Zhang, Xuefeng; Chen, Yulong (Frontiers in Molecular Biosciences, 2025)
Swimming is a whole-body aerobic exercise that has preventive and therapeutic effects on chronic metabolic diseases triggered by a high-fat diet. SPF grade rats (n = 48) were selected. They were divided into 4 groups (GB, GY, ZY and ZB) with 12 rats in each group. The GB and GY groups were fed high-fat chow during the pre-test period, and the ZY and ZB groups were fed normal chow. Swimming training was carried out in ZY and GY groups and no swimming exercise in GB and ZB groups in the later part of the trial. Histopathological staining was performed on the cecum and liver of 48 rats. Physiological and biochemical indices such as ACP, ALP and AST were measured in the blood of the rats in each group, and 6 samples of cecum contents were taken from each group for metagenomics and widely targeted metabolomics. The results showed that AST, ALP, ACP, LDL, IL-6, TNF-α, and IL-1β were significantly lower in the GY group than in the GB group; the structural liver lesions were severe in the GB and GY groups; and the ZY group had higher levels of Prevotellaceae, Muribaculaceae, and Spirochaetes. In comparison with the GB group, the GY group showed significant increases in metabolites associated with metabolic pathways such as ABC transporters and sulfur metabolism. The results show that feeding high-fat diet can cause tissue and organ lesions, cecal microbe and metabolite structure changes in rats. However, swimming training increased the content of beneficial microorganisms and metabolites in rats’ cecum. This study provides a theoretical basis for swimming exercise to alleviate metabolic disorders caused by high fat diet.